1987
DOI: 10.1002/bjs.1800740522
|View full text |Cite
|
Sign up to set email alerts
|

Sliding flap advancement for the treatment of high level fistulae

Abstract: The technique of sliding flap advancement for the treatment of high anal fistulae is described. The technique is not suitable for cases with an acute abscess and is reserved for patients with a well-established chronic fistula track. Thirty patients with anal fistulae were treated by sliding flap advancement from 1980 to 1984. Twenty-nine patients had satisfactory results. With a follow-up ranging from 18 months to 4 years no recurrence of fistulae or abscess were observed. The advantages of the advancement fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
4

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 5 publications
2
39
0
4
Order By: Relevance
“…The MAF is associated with a higher morbidity and significant risk of worsening incontinence (0%-52%) [36][37][38][39] . The AFP is associated with less damage.…”
Section: Discussionmentioning
confidence: 99%
“…The MAF is associated with a higher morbidity and significant risk of worsening incontinence (0%-52%) [36][37][38][39] . The AFP is associated with less damage.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques have been described including fistulotomy [1][2][3][4], fistulectomy [5] and advancement flap procedures [6][7][8][9][10][11]. The results of fibrin glue treatment have been disappointing and the technique has largely been abandoned [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Jones et al [9] describe a technique which is similar in principle to ours for high transsphincteric and suprasphincteric anal fistulae, in which the tract is cored out and the internal opening of the fistula is excised and then a rectal advancement flap is raised to cover the created raw area. Wedell et al [10] confirmed the efficacy of a similar technique for the treatment of high-level fistulae. The external wound is left open for drainage.…”
Section: Discussionmentioning
confidence: 88%